Contrastive study of German and Malay modal verbs formation process - Mohd Jalis, Farhana Muslim (2015)
Acquiring a foreign language is not an easy task especially when the target language differs greatly from the source language particularly in its grammatical system. As such, learning the basic German verb is definitely a challenge for Malaysian language learners due to the typological differences as German is an inflectional language while Malay is an isolating language. For instance, when constructing a German modal verb in a sentence, inexperienced learners may face many challenges due to the differences in word formation process. This study aims to identify the components of German modal verb formation process used by editors in a set of eleven editorial columns of KL-POST 2012 magazines (a magazine published for the German speaking society in Kuala Lumpur) by contrasting them with the Malay modal verbs (kata bantu ragam). Data were collected and analysed using Whitman’s (1970) model and made predictions on the results of the comparison made using Stockwell’s et al., (1965) ‘hierarchy of difficulty’. This study may have implications on both the learning and teaching of German as it provides better understanding for learners to form correct sentences in German. Findings reveal that differences and similarities exist in the formation process when German and Malay modal verbs are contrasted. In addition, by using Stockwell’s et al., (1965) ‘hierarchy of difficulty’ to make predictions, it was found that modal verbs may cause difficulties in language learning. Based on these findings, it can be concluded that understanding the differences and similarities may provide alternative explanations that can assist learners’ comprehension, and it is important for educators to provide more explanation on the use of modal verbs in their lessons. This study can act as a guide for language instructors to prepare more effective teaching plans that will provide better explanations for morphologically inexperienced learners.